The effectiveness of physical activity in asthma management: An overview of systematic reviews - Wenrui Liu; Zhenzhen Feng; Shangyue Song; Siyuan Lei (PLoS ONE, 2025)
Background Physical activity (PA) has become a promising complementary non-pharmacological intervention to improve exercise capacity, cardiopulmonary fitness, and quality of life in individuals with asthma. This overview systematically consolidates existing evidence to assess the clinical viability of physical activity as a scalable supplementary therapy for asthma management. Methods We searched 12 electronic databases to identify systematic reviews (SRs) from inception until February 12, 2025, concerning the efficacy of physical activity in asthma management. Literature was independently reviewed, data extracted and verified by two researchers. A third author was designated to mediate any disputes concerning screening. The methodological quality of SRs was assessed using the A Measurement Tool to Assess SRs 2 (AMSTAR 2) checklist, and the certainty of evidence for key outcomes was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework. Results This study analyzed 34 SRs (published 2000–2024) that included quantitative synthesis involving 113–2280 participants from asthma populations: adults (9 SRs), children (8 SRs), and mixed adult-child cohorts (17 SRs), with disease severity varying from mild to severe. Ten SRs were assessed as moderate to high quality by AMSTAR 2, whereas the other SRs were classified as low or very low quality. We evaluated the quality of evidence for SRs utilizing the GRADE evidence quality assessment framework. Thirteen moderate-quality evidence, and 51 low or very low-quality evidence support the improvement of PA on the outcomes of asthma quality of life, asthma control, lung function, exercise capacity, and respiratory muscle strength. Conclusion Engagement in physical activity has been demonstrated to markedly enhance asthma-related outcomes. Specific interventions provide targeted advantages in various domains: aerobic exercise enhances AQLQ scores and lung function metrics, including FEV1, FVC, PEF; breathing exercises improve AQLQ, FVC, and PImax; yoga correlates with enhancements in AQLQ, FEV1, and FVC; aquatic exercise results in increased FEV1; and inspiratory muscle training yields improvements in FEV1, FVC, PEF, and PImax. Nonetheless, there exists an imperative requirement for more stringent studies to fortify the existing evidence base. Furthermore, due to the significant individual variability among asthma patients, the creation of personalized exercise prescriptions is expected to produce enhanced clinical results.